Experimental study on thermochemical composite flooding mechanism of extra heavy oil reservoirs with erosion channels - Cao, Qiuying; Zheng, Haoyu; Yu, Jianmei; Xiong, Zanfu; Wei, Tao; Zhu, Shuainan; Liu, Ruixin (Frontiers in Energy Research, 2024)
During the steam flooding of extra heavy oil, expansion of steam chamber is difficult and erosion channels appear, which is different from conventional heavy oil. The thermochemical composite system composed of steam, foam and viscosity reducer can effectively improve the development effect of extra heavy oil reservoirs. However, during the thermochemical composite flooding, the rheological characteristics of extra heavy oil and the influence of erosion channels on oil displacement mechanism are not yet researched. Taking the extra heavy oil reservoir in Block X of the Chunfeng Oilfield as an example, experimental research on the rheological properties and thermochemical composite flooding of extra heavy oil model with erosion channel is conducted. Firstly, the influence of thermochemical composite system on the rheological properties of extra heavy oil is evaluated. Then, a one-dimensional(1D) sand-pack model with erosion channel is used to conduct thermochemical composite flooding experiments, comparing the recovery of steam flooding, foam assisted steam flooding, viscosity reducer assisted steam flooding, and composite flooding (foam and viscosity reducer assisted steam flooding). Finally, a two-dimensional (2D) sand-pack model with erosion channel is used to conduct thermochemical composite flooding experiments, comparing the recovery of viscosity reducer assisted flooding and composite flooding. The results show that viscosity reducer reduces the viscosity of extra heavy oil greatly, and the extra heavy oil is not sensitive to the change of temperature after viscosity reduction. When the concentration of viscosity reducer is 0.4% or more, good viscosity reduction effect can be achieved at different oil-water ratio. In the 1D sand-pack model experiments, compared to steam flooding, foam assisted steam flooding, viscosity reducer assisted steam flooding, and composite flooding, the recovery increased by 4.38%, 17.38%, and 30.46%, respectively. In the 2D sand-pack model experiments, compared to steam flooding, the viscosity reducer assisted steam flooding and composite flooding increase the oil recovery by 12.49% and 16.61%, respectively. The thermochemical composite flooding of extra heavy oil is dominated by erosion, supplemented by displacement. There is a synergistic effect between chemicals in the process of composite flooding. At the same time, the purpose of “enhanced erosion and expanded sweep" is achieved.